Commencing Deep Seabed Mining: A Review on Law No. 3 of 2020 on Mineral and Coal Mining - Tobias, Evan (Faculty of Law, Universitas Brawijaya, 2022)
In 2020, the Government of Indonesia enacted Law No. 3 of 2020 on Mineral and Coal Mining, which amended Law No. 4 of 2009 on Mineral and Coal Mining. Under this amendment, Law No. 3 of 2020 on Mineral and Coal Mining expands the definition of mining law territories, as stipulated under Article 1, number 28a. This provision covers the mining law territories of the Indonesian archipelago, seabed area, and continental shelf. This study explores the legal consequences of the term “seabed area” in Law No. 3 of 2020 on Mineral and Coal Mining, to determine whether the law paves the way for deep seabed mining. Through normative and descriptive approaches, this study found that despite the broader definitions of mining territories, Law No. 3 of 2020 on Mineral and Coal Mining is insufficient to initiate deep seabed mining. This is because seabed mining requires a detailed governance structure, especially on the rights and duties of every party involved. Therefore, this paper recommends that the activity be regulated by a distinctive law that specifically addresses seabed mining.